2017
DOI: 10.1002/mnfr.201700260
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid modulates cancer‐associated micro RNAs and inflammatory mediators in neoplastic and non‐neoplastic colonic cells in a different way

Abstract: The different effects of high-physiological FA concentrations in malignant and non-malignant colonic cell lines regarding cancer-associated miRNAs and inflammatory mediators may contribute to the different effects of FA supplementation on colonic carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…High-dose folic acid supplementation or high circulating levels of folic acid in healthy young individuals as well as in obese post-menopausal women were associated with reduced numbers and cytotoxicity of natural killer cells and altered expression profiles of cytokines [68,69]. Exposure of human colonic cell lines to increasing doses of folic acid resulted in altered expression of inflammatory mediators, with effects differing for nonmalignant and malignant cell lines [70]. The relationship between high folic acid intake and reduced natural killer cell cytotoxicity was also confirmed in murine studies and was, at least partially, attributed to reduced interleukin (IL)-10 production with excess folic acid [71].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose folic acid supplementation or high circulating levels of folic acid in healthy young individuals as well as in obese post-menopausal women were associated with reduced numbers and cytotoxicity of natural killer cells and altered expression profiles of cytokines [68,69]. Exposure of human colonic cell lines to increasing doses of folic acid resulted in altered expression of inflammatory mediators, with effects differing for nonmalignant and malignant cell lines [70]. The relationship between high folic acid intake and reduced natural killer cell cytotoxicity was also confirmed in murine studies and was, at least partially, attributed to reduced interleukin (IL)-10 production with excess folic acid [71].…”
Section: Discussionmentioning
confidence: 99%
“…While high-physiological FA concentration had no influence on promoter methylation, in the HT29 cell line, tumor-suppressive micro RNAs were predominantly downregulated and the expression of genes involved in chemotaxis and immunity was modulated. In non-malignant HCEC cells folic acid didn’t affect pro-inflammatory genes and cancer-associated microRNA expression [ 166 ]. Some studies demonstrated that DNA methylation may be considered as a biomarker of colorectal cancer and that methylation of DNA in the colonic tissues and leukocytes can be increased by supplementation with folic acid [ 143 , 167 , 168 ].…”
Section: Problem Of Folate Deficiency and Oversupplementationmentioning
confidence: 99%
“…FA plays a critical role in de novo synthesis of nucleic acid synthesis and biological methylation [ 5 ], and it is related to maintaining the health of the human genome. FA deficiency is therefore hypothesized to contribute to CRC through disruption of these processes [ 6 , 7 ], and moderate amounts of FA can protect the normal colorectal mucosa [ 8 , 9 ]. Inversely, the excessive intake of FA may accelerate the progression of precancerous tissues to malignancy [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%